Digital Genocide Criminal Responsibility for Exploiting Cyberspace as a Means to Commit Genocidal Crimes under Criminal Law - Al-Nouri, Nada (Journal of Legal Sciences, 2026)
The research highlights the phenomenon of digital genocide as one of the emerging criminal patterns in which cyberspace is utilized as a tool for committing acts of genocide through the ideological indoctrination of hatred against other identities and the digital mobilization aimed at discriminating against them and excluding them from the sphere of social participation. The significance of this study emerges from the increasing danger posed by extremist groups in their use of digital technologies, including what Iraq witnessed through the practices of the ISIS terrorist organization against the Yazidi community and other components, where such practices combined field operations with digital means in carrying out genocidal acts. The study adopts a criminal-law approach to clarify the concept of digital genocide, define its parameters, and compare it with traditional forms of genocide. It further examines the motives and factors that make cyberspace a fertile environment for the commission of such crimes—whether due to the speed of dissemination, the difficulty of monitoring, or the direct influence exerted on public opinion. The research also addresses the resulting consequences, such as the fragmentation of national and religious identity, ultimately facilitating displacement and physical liquidation. On the analytical level, the research explores the criminal classification (legal characterization) of these acts within the framework of Iraqi law, identifying gaps in national legal provisions—whether in the Penal Code or in legislation related to terrorism and cybercrimes. It also outlines the direction of criminal policy in combating this pattern of criminality in accordance with the methodology of the 1948 Convention on the Prevention and Punishment of the Crime of Genocide. The study concludes that confronting digital genocide requires the development of the Iraqi legislative system, strengthening judicial and security cooperation with the international community, and establishing regulatory and legal mechanisms capable of prosecuting perpetrators and preventing the exploitation of cyberspace as a platform for genocide. It further emphasizes the necessity of imposing liability on platform owners as partners in the digital conduct carried out through their platforms—even when they do not consent to such conduct—since allowing the continuous commission of acts related to digital genocide places them within the scope of criminal responsibility.